Copper oxide nanostructured thin films processed by SILAR for optoelectronic applications. Issue 51 (16th November 2022) - Patwary, Md Abdul Majed; Hossain, Md Alauddin; Ghos, Bijoy Chandra; Chakrabarty, Joy; Haque, Syed Ragibul; Rupa, Sharmin Akther; Uddin, Jamal; Tanaka, Tooru
Abstract : Cu x O nanostructured thin films are potentially appealing materials for many applications. The deposition technique, SILAR, explored in this paper offers many advantages. Abstract : The lack of high-functioning p-type semiconductor oxide material is one of the critical challenges that face the widespread performance of transparent and flexible electronics. Cu x O nanostructured thin films are potentially appealing materials for such applications because of their innate p-type semi-conductivity, transparency, non-toxicity, abundant availability, and low-cost fabrication. This review summarizes current research on Cu x O nanostructured thin films deposited by the SILAR technique. After a brief introduction to the advantages of Cu x O semiconductor material, diverse approaches for depositing and growing such thin films are discussed. SILAR is one of the simplest deposition techniques in terms of better flexibility of the substrate choice, the capability of large-area fabrication, budget-friendly, deposition of stable and adherent film, low processing temperature for the film fabrication as well as reproducibility. In addition, various fabrication parameters such as types of copper salts, pH of precursors, number of cycles during immersion, annealing of as-deposited films, doping by diverse dopants, and growth temperature affect the rate of fabrication with the structural, electrical, and optical properties of Cu x O nanostructured thin films, which led the technique unique to study extensively. This review will include the recent progress that has recently been made in different aspects of Cu x O processed by the SILAR. It will describe the theory, mechanism, and factors affecting SILAR-deposited Cu x O. Finally, conclusions and perspectives concerning the use of Cu x O materials in optoelectronic devices will be visualized.